Cognitive reserve in bipolar disorder: relation to cognition, psychosocial functioning and quality of life. (30th December 2015) - Anaya, C.; Torrent, C.; Caballero, F. F.; Vieta, E.; Bonnin, C. del Mar; Ayuso‐Mateos, J. L.; ,
Abstract : Objective: Cognitive reserve (CR) is a concept that was postulated as a protective factor for some clinical symptoms after the observation that there is not a direct relationship between the degree of brain damage and its clinical manifestation. This study aimed to explore the association between CR and the main outcomes in bipolar disorder (BD): cognitive functions, psychosocial functioning and perceived quality of life. Method: A sample of 224 euthymic bipolar patients was assessed with a neuropsychological battery, the Functioning Assessment Short Test and the Medical Outcomes Study 36‐Item Short‐Form Health Survey (SF‐36). CR was calculated through three proxies: estimated premorbid Intelligent Quotient, educational level and occupational attainment. Relationships between CR and cognitive functions, psychosocial functioning and quality of life were assessed by multiple linear regression models. Results: Higher CR was associated with better cognitive functioning ( P < 0.001 in processing speed, working memory, verbal and visual memory, and executive function; P = 0.026 in attention) and better psychosocial functioning ( P = 0.008). For quality of life, CR was positively associated with the physical component of the SF‐36 ( P = 0.016) but negatively associated with the mental component ( P = 0.004). Conclusion: The results suggest that CR may play an important role in the course and prognosis of bipolar patients and it should be considered in both clinical and research settings related to BD.